Scalable synthesis of cladosporin - Das, Pronay; Mankad, Yash; Reddy, D. Srinivasa (Tetrahedron Letters, 2019)
Cladosporin, a secondary metabolite isolated from fungal sources like Cladosporium cladosporioides and Aspergillus flavus was found to exhibit selective nano-molar activity against malarial parasite Plasmodium falciparum by inhibiting parasitic protein biosynthesis. In addition, this natural product has a broad range of bioactivities including, antiparasitic, antifungal, antibacterial as well as plant growth inhibition. However, it has limited availability from the natural sources for further development. Herein, we report a modified and improved synthetic route which led us to produce this potent natural product in a gram scale. Conversion of the undesired diastereomer to desired one via Mitsunobu inversion of secondary alcohol and carbon monoxide insertion reaction towards the construction of isocoumarin unit are the key features of the present synthesis. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Anti-malarials; Cladosporin; Mitsunobu; Total synthesis

Design, synthesis, and structural analysis of cladosporin-based inhibitors of malaria parasites - Babbar, Palak; Das, Pronay; Manickam, Yogavel; Mankad, Yash; Yadav, Swati; Parvez, Suhel; Sharma, Amit; Reddy, Srinivasa (ACS Infectious Diseases, 2021)
Here we have described a systematic structure activity relationship (SAR) of a set of compounds inspired from cladosporin, a tool compound that targets parasite (Plasmodium falciparum) lysyl tRNA synthetase (KRS). Four sets of analogues, synthesized based on point changes in the chemical scaffold of cladosporin and other logical modifications and hybridizations, were assessed using high throughput enzymatic and parasitic assays along with in vitro pharmacokinetics. Co-crystallization of the most potent compound in our series (CL-2) with PfKRS revealed its structural basis of enzymatic binding and potency. Further, we report that CL-2 has performed better than cladosporin in terms of metabolic stability. It thus represents a new lead for further optimization toward the development of antimalarial drugs. Collectively, along with a lead compound, the series offers insights on how even the slightest chemical modification might play an important role in enhancing or decreasing the potency of a chemical scaffold.

Herbicidal bio-assay of isocladosporin enantiomers and determination of its plausible absolute configuration - Mankad, Yash; Das, Pronay; Pathan, Ejaj; Deshpande, V. M.; Reddy, D. Srinivasa (Journal of Antibiotics, 2021)
A fungal metabolite, isocladosporin was isolated from natural fungus, Cladosporium cladosporioides in the mid of 90s. Due to the lack of optical rotation of isolated natural product sample, the absolute configuration of the natural product remained undetermined for more than two decades. Herein, we demonstrated an SAR study of enantiomers of isocladosporin in herbicidal bio-assay against wheat coleoptile. Using this study as a comparative tool we further proposed the plausible absolute configuration of natural isocladosporin for the first time. The assigned configuration was also supported through biogenetic precursors.

Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.